2D and 3D coexisting modes of thermal convection in fractured hydrothermal systems - Implications for transboundary flow in the Lower Yarmouk Gorge. (December 2016) - Magri, F.; Möller, S.; Inbar, N.; Möller, P.; Raggad, M.; Rödiger, T.; Rosenthal, E.; Siebert, C.
Abstract: Numerical investigations of 2D and 3D modes of large-scale convection in faulted aquifers are presented with the aim to infer possible transport mechanisms supporting the formation of thermal springs through fractured aquicludes. The transient finite elements models are based on idealized structural features that can characterize many hydrothermal systems. The sensitivity analysis of the fault permeability showed that faults cross-cutting the main regional flow direction allow groundwater to be driven laterally by convective forces within the fault planes. Therein thermal waters can either discharge along the fault traces or exit the fault through adjacent permeable aquifers. In the latter case, the resulting flow is helicoidally and transient. The location and the spacing between discharge areas can migrate with time, is not strictly constrained to the damage zones and reflects the wavelength of the multicellular regime in the fault zone. An illustrative example based on simplified structural data of the Lower Yarmouk Gorge (LYG) is presented. The numerical calculations indicate that crossing flow paths result from the coexistence of fault convection, developing for example along NE-SW oriented faults within the Gorge, and additional flow fields. The latter are induced either by topography NS gradients, e.g. perpendicular to the major axe of the Gorge, or by local thermal convection in permeable aquifers below the Eocene aquiclude. Sensitivity analysis of fault hydraulic conductivity ( K ) and the analytical solutions based on viscous-dependent Rayleigh theory show that K values between 2.3e −7 m/s and 9.3e – 7 m/s (i.e. 7 m/yr and 30 m/yr, respectively) favor coexisting transport processes. The uprising thermal plumes spread over several hundred meters forming clusters of springs, in agreement with observation, and which temperature fall within the measured ranges, i.e. 20 °C−60 °C. To some extent the models also reproduced the transient behavior of the spring temperature. Owing to the idealized nature of the presented models, the numerical results and the associated analytical solution can be applied to study the onset of thermal convection and resulting flow patterns of any fractured hydrothermal basin. Graphical abstract: Highlights: Co-existing modes of flow transport processes are favored in faults. A viscous-dependent Rayleigh theory for faulted systems is given. In the LYG low fault permeability is sufficient to generate springs. Fault permeability range allowing transboundary flow across the LYG is given.